COVID-19 in Zambia: Impacts on Production, Poverty & Food Systems - Pauw, Karl; Tembo, Bernard; Thurlow, James (2021)
Karl Pauw1, Bernard Tembo2 & James Thurlow1 1. International Food Policy Research Institute (IFPRI) 2. Zambia Institute of Policy Analysis and Research (ZIPAR) Last updated: 6 April 2021